Mass transfer characteristics and concentration field evolution for gas-liquid Taylor flow in milli channels. (2nd November 2019) - Abiev, R.Sh.; Butler, C.; Cid, E.; Lalanne, B.; Billet, A.-M.
Graphical abstract: Highlights: Mass transfer of gas-liquid Taylor flow in milli channels is analysed. Small scale convection by Taylor vortices in the liquid slugs plays a key role. Periodical nature of liquid mass transfer is directly linked to global transfer rate. kL a is proportional to circulation frequency in liquid slugs in most conditions. Influence of flow behavior at T-mixer on the concentration patterns is discussed. Abstract: The results of the recent experimental work performed by Butler et al. (2016, 2018) are analysed based on the dominant phenomena: (i) small scale convection by means of Taylor vortices in the liquid slugs and (ii) diffusion in lubrication film. A main result shown here is that the Taylor circulation frequency is able to reflect the global mass transfer rate in gas-liquid Taylor flow through an almost linear relationship, which emphasizes the interest of the circulating motion in the slug, and gives a very simple correlation to predict the k L a value (at large Schmidt number). A mechanism of flow behavior during the bubble formation at the T-mixer is proposed as a possible explanation of unexpected concentration areas (called "islands"). However, despite of these unusual concentration field structures in these cases, the mass transfer rate coefficient k L a is still accurately predicted by the Taylor circulation frequency in the slug.